2009
DOI: 10.1007/s11274-009-0157-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant Staphylococcus aureus in diabetics clinical samples

Abstract: Antibiotic resistance in 40 Staphylococcus aureus clinical isolates from 110 diabetic patients (36%) was evaluated. Of these, 32 (80%) of the isolates showed multidrug-resistance to more than eight antibiotics and 35% isolates were found to be methicillin resistant S. aureus (MRSA). All 40 S. aureus strains (100%) screened from diabetic clinical specimens were resistant to penicillin, 63% to ampicillin, 55% to streptomycin, 50% to tetracycline and 50% to gentamicin. Where as low resistance rate was observed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a study on prevalence of MDRSA in diabetics clinical samples by Raju et al, (2010) 40% Staphylococcus aureus strains were found to be MDR. In a study conducted in healthy preschool children in Ujjain, India the Nasal Carriage and Antimicrobial Susceptibility of S. aureus among the 16 MRSA isolates 3 (19%) were MDR which is similar to our result (Ashish Pathak et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In a study on prevalence of MDRSA in diabetics clinical samples by Raju et al, (2010) 40% Staphylococcus aureus strains were found to be MDR. In a study conducted in healthy preschool children in Ujjain, India the Nasal Carriage and Antimicrobial Susceptibility of S. aureus among the 16 MRSA isolates 3 (19%) were MDR which is similar to our result (Ashish Pathak et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However resistance is not only related to aminoglycoside antibiotics like vancomycin, there are S. aureus strains resistant to methicillin that are also resistant to practically all β-Lactam group (penicillin, oxacillin, ampicillin, amoxicillin and augmentin), and macrolides (clindamycin and azithromycin). These multidrug-resistant strains are spreading outside hospitals and represent a serious concern [31] and sensitive to the aminoglycoside group (amikacin), macrolide antibiotics (nitrofurantoin) and the quinolone group (ciprofloxacin, ofloxacin and norfloxacin) [32][33][34][35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Park et al and Shyh‐Ming et al reported that diabetic animals with S. aureus infection exhibit a delayed inflammatory response and increased production of cytokines, which leads to development of immune complications. Recently, the increase in multidrug resistance is making treatment of S. aureus infections with antibiotics increasingly challenging …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the increase in multidrug resistance is making treatment of S. aureus infections with antibiotics increasingly challenging. 6 Historically, various types of wound dressing materials have been used to treat skin ulcers. Peng et al 7 manufactured an alginate hydrogel into a fibrous structure with interconnected pores and demonstrated that it is a suitable material for skin wound dressing.…”
Section: Introductionmentioning
confidence: 99%